TRENDS IN USE OF THE STEPPE LAND RESOURCES OF STAVROPOL REGION IN DIFFERENT PERIODS OF THE AGRARIAN ECONOMY - Elena V. Pismennaya; Vladimir A. Stukalo (Юг России: экология, развитие, 2017)
Abstract. The aim of this work is to examine trends in the development of agriculture and its industries, land and primary production on the territory of the steppe zone of Stavropol region during the natural history period (18502016). The analysis allows us to identify the main periods of evolution of land use and environmental and economic problems, as well as measures to overcome them. Methods. The following structure "nature – society – economy" describes the analytical and mathematical models. The structure of land use is described as the system "nature – society – economy" and is reflected in the analytical and mathematical models. They provide insight into the dynamics of change in quantitative indicators (area of agricultural areas and wetlands, crop yields, basic agri-environmental data, etc.) and qualitative transformation of the latter (the presence of erosive and deflationary processes and other phenomena). In addition, careful attention is paid to the managerial decisions and activities, as well as opportunistic and market factors that influence the dynamics of the above changes during the period under review. To adjust for land development it is very important to pay attention on climatic conditions, which recently have a tendency to significant changes. Results. Analysis of economic development of the steppe areas allows to determine the structuralfunctional model of land use, to identify the main environmental and economic factors influencing its development. Main conclusion. This approach allows us to correct managerial decisions, stabilizing land use in the industrial sector.